Changes in blood glucose and lipid metabolism levels in children with central precocious puberty and its correlation with obesity - Xin Cui; Xin Cui; Xin Sun; Qiubo Li; Zongbo Chen (Frontiers in Pediatrics)
ObjectiveThis study analyzed the changes in blood glucose and lipid metabolism levels in children with central precocious puberty (CPP) and the correlation between CPP and obesity.MethodsIn total, 88 children with CPP aged 6–10 years who were admitted to our hospital between January 2023 and June 2024 (the CPP group), and 88 children without CPP in the same age group who received health check-ups (the non-CPP group) were retrospectively enrolled in this study. General data [gender, age, bone age, and body mass index (BMI)] were collected. Levels of blood glucose metabolism indicators [fasting plasma glucose (FPG), 2-h postprandial blood glucose (2hPG), and hemoglobin A1c (HbA1c)] and blood lipid metabolism indicators [triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C)] were compared. The incidence of obesity was calculated, and the Tanner stages of the obese group and the non-obese group were compared. The correlation between CPP degree (measured by Tanner staging) and obesity degree (measured by BMI) was analyzed using Spearman’s correlation analysis.ResultsThe differences in gender and age between the CPP and non-CPP groups were insignificant (P > 0.05). Bone age and BMI in the CPP group were higher than in the non-CPP group (P < 0.05). The CPP group had higher serum FPG, 2hPG, HbA1c, TG, TC, and LDL-C levels and lower serum HDL-C levels than the non-CPP group. The incidence of obesity was higher in the CPP group (21.59%, 19/88) than in the non-CPP group (6.82%, 6/88). The Tanner staging scores in the obese group for the boys (testes and pubic hair), girls (breasts and pubic hair), and as a whole (testes/breasts and pubic hair) were elevated compared to those in the non-obese group (P < 0.05). Spearman’s correlation showed that the CPP degree (measured by Tanner staging) was positively correlated with the obesity degree (measured by BMI) in boys, girls, and the study sample as a whole (P < 0.001).ConclusionChildren with CPP had abnormal levels of blood glucose and lipid metabolism, and the CPP degree in these children was positively correlated with the degree of obesity.